Tyrosine Dephosphorylation of ASC Modulates the Activation of the NLRP3 and AIM2 Inflammasomes - Mambwe, Bezaleel; Neo, Kurt; Javanmard Khameneh, Hanif; Leong, Keith Weng Kit; Colantuoni, Mariasilvia; Vacca, Maurizio; Muimo, Richmond; Mortellaro, Alessandra (Frontiers in Immunology, 2019)
The inflammasome is an intracellular multi-protein complex that orchestrates the release of the pro-inflammatory cytokines IL-1β and IL-18, and a form of cell death known as pyroptosis. Tyrosine phosphorylation of the inflammasome sensors NLRP3, AIM2, NLRC4, and the adaptor protein, apoptosis-associated speck-like protein (ASC) has previously been demonstrated to be essential in the regulation of the inflammasome. By using the pharmacological protein tyrosine phosphatase (PTPase) inhibitor, phenylarsine oxide (PAO), we have demonstrated that tyrosine dephosphorylation is an essential step for the activation of the NLRP3 and AIM2 inflammasomes in human and murine macrophages. We have also shown that PTPase activity is required for ASC nucleation leading to caspase-1 activation, IL-1β and IL-18 processing and release, and cell death. Furthermore, by site-directed mutagenesis of ASC tyrosine residues, we have identified the phosphorylation of tyrosine Y60 and Y137 of ASC as critical for inflammasome assembly and function. Therefore, we report that ASC tyrosine dephosphorylation and phosphorylation are crucial events for inflammasome activation.